Strategi Komunikasi Krisis Studi Kasus Gus Miftah Dalam Menanggapi Isu Hinaan Terhadap Tukang Es Teh Di Instagram - Kudrawi, Ahmad Hafiizh; Ikhsan, M Rafli; Razzaq, Abdur; Nugraha, Muhammad Yudistira (Komunika : Jurnal Ilmiah Komunikasi, 2025)
The development of social media has changed the pattern of public interaction and accelerated the spread of information, including in the context of crisis communication. This study analyzes the crisis communication strategy implemented by Gus Miftah, a religious and public figure, in responding to netizens' criticism of his statement that was considered insulting to an iced tea seller in an event that went viral on Instagram in December 2024. This study uses a descriptive qualitative approach with a content analysis method on data obtained from documentation of social media uploads, online news, Gus Miftah's public statements, and public responses on digital platforms. The results of the study indicate that the crisis communication strategy implemented through the use of an Instagram account by posting content that includes an open apology, personal clarification, direct meetings with the injured party, and resignation from public office. This approach is in line with the Situational Crisis Communication Theory (SCCT) which emphasizes the importance of a response that is appropriate to the type of crisis being faced. This study concludes that the combination of corrective and restorative strategies carried out by Gus Miftah has proven effective in mitigating the crisis and restoring some public trust. This finding can be a reference for other public figures in dealing with reputation crises in the digital era.